Sutan Takdir Alisjahbana's Thinking, Today and in the Future. Sutan Takdir Alisjahbana as a Literary Writer. - E. Ulrich Kratz (HISKI, 2008)
Until today, the discussion over Sutan Takdir Alisjahbana's works has still been controversial. On one hand, he was considered pro-West and anti-East, while on the other he was respected as a visionary and a man of principle whose contributions to 20